THE TREATMENT OF MULTIPLE MYELOMA PATIENTS NOT ELIGIBLE FOR ASCT - Anuj Mahindra; Jacob Laubach; Paul Richardson; Constantine Mitsiades; Robert Schlossman; Irene Ghobrial; Teru Hideshima; Noopur Raje; Nikhil Munshi; Kenneth Anderson (Mediterranean Journal of Hematology and Infectious Diseases)
Advances in therapies for younger patients with multiple myeloma have resulted in significant improvements in outcome over recent years, on the contrary the progress in treatments for elderly patients has remained more modest. Traditionally, patients who are not eligible for transplantation, like the older patients, have been treated with the combination of melphalan plus prednisone (MP), which leads to responses in approximately 50% of patients; however, patients rarely achieve a complete response (CR) and long-term outcomes are disappointing, with a relapse-free survival of approximately 18 months and an overall survival (OS) of approximately 3 years. With the arrival of novel agents, including the first–in-class proteasome inhibitor, bortezomib, and the immunomodulatory agents, thalidomide and lenalidomide, a shift in the management of older patients and/or those not eligible for transplantation has taken place. Increasingly, novel agents are now being incorporated into therapy, based on the positive findings from clinical trials in this setting, and outcomes have improved accordingly.